The role of the choice of sample size and type in controlling the results of scientific research - Saadeddine, Habiba (Journal of Social Sciences and Humanities, 2023)
This study aimed to shed light on the importance of determining the size of the sample, as well as choosing its type in order to reach more accurate and credible results that can be generalized to the study population. This study concluded that there are several ways to choose the sample size and determine its type. This selection goes through several stages, and is controlled by a number of factors. This study also found that the success of scientific research is largely related to the researcher’s good choice of studied sample’s type and size.